Study on endometrial cancer patients and their treatment outcome in BPKMCH - Pandey , Manju; Acharya , Bijaya Chandra; Subedi , Hemnath; Gurung , Sarita Rana; Pariyar , Jitendra; Paudel , Shivajee; Pandey , Greta; Paudel , Nitu; Upadhyay , Hari Prasad; Shrestha, Binuma; Tiwari , Damodar (Europasian Journal of Medical Sciences, 2021)
Background: There are few studies on endometrial carcinoma in Nepal so present study aims to evaluate the clinicopathologic characteristics of endometrial cancer patients along with their treatment outcome. Material and Methods: This is a descriptive study conducted from January 2011 to December 2020 and all patients of endometrial carcinoma who had undergone primary surgery at B.P. Koirala Memorial Cancer Hospital were included. Socio-demographic characteristics, clinical presentations, histologic type, treatment modalities and outcomes were obtained and analyzed. Results: The mean age was found to be 58 8.32 years. Most were postmenopausal accounting for 86%. Medical co-morbidities were associated in 40% of patients. Most common presentation was postmenopausal bleeding seen in 68% of patients. Total abdominal hysterectomy and bilateral salpingo-oophorectomy was done in 48% of patients. The main histologic type was endometrioid carcinoma observed in 96% of patients. Low grade carcinoma was found in 78% of patients out of which grade 1 accounting for 50% and rest grade 2 while high grade carcinoma was found 22% of patients. 64% of patients required adjuvant therapy. Recurrence was seen in 16% of patients. Conclusions: Endometrial carcinoma is common in post menopausal age group. Endometrioid variety is the commonest histologic type. Clinicopathologic characters of endometrial carcinoma affect the prognosis of the patient. DOI: https://doi.org/10.46405/ejms.v3i2.382